Group Discussion and Booklet for Tuberculosis Prevention in Manado - Elne Vieke Rambi; Ketrina Konoralma; Dionysius Sumenge (Jurnal Kesehatan Masyarakat, 2023)
The purpose of the study was to determine the effect of using focus group discussions and booklets for the prevention of tuberculosis in Manado. Type of Research "A quasy experimental design with Pre and Post Test Group ". The population is tuberculosis patients who seek treatment at the Public Health Center as many as 200 cases. Samples were taken using the Slovin formula and met the inclusion criteria of 113 respondents. Collecting data by providing counseling using booklets, and Group Disccussion. The data was processed using the "Wilcoxon Test" statistical test. The results showed that the gender of women was 69(61%), high school education 66(58,4%), housewife occupation 43(38,1%), average age 43,75+Std.15,095. Result of research: cause of pre test 96(85%), post test 105(92,92%) p0,000, pre test 63(55,8%) post test 90(79,64%), p0,000; source of pre-test transmission 75(66.4%) post-test 91(80.53%), p0.000, risk of pre-test transmission 67(53.9%), post-test 93(82.30%) p0.000, seeking treatment pre test 97(85.8%, post test 109(96.46%), p0.000, prevention pre test 75(66.4%), post test 101(89.38%), p0.000, recovery pre test 109(96.5%) post test 107(94.7%) p0.000, treatment 107(94.7%), post test 110(97.34%), p0.000, nutritious food pre test 100(88.5%) post test 105(92.92%), p0.000.- Conclusion: There is a very significant effect between the use of focus group discussions and booklets in improving the knowledge, attitudes and behavior of respondents. Suggestion: Continue to carry out health education to improve the knowledge, attitudes and behavior of patients.